STUDI IMPLEMENTASI PROGRAM KESEHATAN IBU DAN ANAK DI PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Febriandini, Ade Putri; Rostyaningsih, Dewi; Rengga, Aloysius; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Primary Health Care (PHC) as a basic level of health care units even categorized as PHC with or non direct services have to implement maternal and child health programme both promotive and preventive care based on The Rule of Health DepartmentNo. 75/2014 on Community Health Centre. This study aimed to obtain information on the implementation of the Maternal and Child Health Program and the factors associated with the implementation of the MCH Program in Tlogosari Kulon Primary Health Care Semarang and usingthe descriptive qualitative research methods to obtain the research aims. The results of this researchshowed that the five basic services are implemented at the primary care level such as antenatal care, postpartum, childbirth, neonatal and neonatal complications have not been carried out in accordance with Permenkes 75 in 2014 due to limited number of midwives and facilities MCH services. Nevertheless, the services related to health of infants and toddlers such as immunization services, visiting of neonatal services and the handling of high-risk infants have been implemented and get a positive response by the people of TlogosariKulon. Analysis of factors associated with the implementation of the MCH Program showed that factors such as budget, human resources and infrastructure services become the main obstacle in the implementation of MCH services in health centers TlogosariKulon Semarang. Based on the results of this research, it is needed some effort to improve the health of mothers and children especially the accuracy of disbursement of operational health centers that still there is a delay. In addition, the number of health personnel such as midwives who do not comply with the rules and revitalization of infrastructure such as infant warmer, incubator and midwife tool.